Web graphics for non designers - Boyce, Nick; Boyce, Nick (Birmingham : glasshaus, 2002)
"Have you ever wished that you could make your web pages look eye catching and professional, as well as having great functionality? Well, look no further. In this book we take you through the basics of web design, demonstrating effective use of color on sites, visual elements that work, and successful use of text. Then we go on to show how to put these elements together to make a well designed, brilliantly laid out web page.
What Makes Web Graphics Work -- Using Color -- How to Use Text Effectively -- Typography -- Visual Elements -- Layout -- File Formats and File Sizes -- Graphics Applications -- Vector Graphics for the Web.
Inludes index
Keywords: Computer graphics; Web sites -- Design